Effect of Magnesium Sulphate with Bupivacaine in Ultrasound-guided Transversus Abdominis Plane Block in patients undergoing Total Abdominal Hysterectomy - Gurung, Nikita; Bista, Navindra Raj; Shrestha, Anil; Shakya, Bigen Man; Acharya, Binita (Journal of Karnali Academy of Health Sciences, 2021)
Background: Transversus abdominis plane block is a valuable component of multimodal analgesia regimen. Magnesium sulphate has been shown to increase the duration of action of different peripheral nerve blocks. We assessed the efficacy of magnesium sulphate as an adjuvant to bupivacaine in transversus abdominis plane block in patients scheduled for total abdominal hysterectomy under general anaesthesia. Methods: Sixty-six patients undergoing total abdominal hysterectomy under general anaesthesia were divided into two groups. Ultrasound guided bilateral transversus abdominis plane block was performed in both group before extubation. Bupivacaine alone group received block with 20ml of 0.25% bupivacaine while Bupivacaine with Magnesium group received block with 20ml of 0.25% bupivacaine with 150mg of magnesium sulphate on each side. Pain scores at 0, 2, 4, 6, 12 and 24 hours postoperatively along with time to first request of analgesia, total consumption of fentanyl and incidence of nausea or vomiting were noted. Results: Group BM showed significantly lower pain scores at 4 and 6 hours (p=0.001 and 0.017 respectively). Time to first request of analgesia was significantly more in Group BM [285 minutes (85, 370) vs. 75 minutes (52.5, 150), (p<0.001)]. Total postoperative fentanyl consumption was significantly less in Group BM (230±59.06 mcg vs. 289.85±69.13 mcg, p<0.001). Conclusions: Bupivacaine with magnesium sulphate in transversus abdominis plane block after total abdominal hysterectomy under general anaesthesia results in lower post operative pain scores, longer duration of analgesia and less postoperative fentanyl requirement with no difference in incidence of nausea/vomiting compared with bupivacaine alone.